2018
DOI: 10.1038/s41419-018-0755-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of excessive autophagy and mitophagy mediates neuroprotective effects of URB597 against chronic cerebral hypoperfusion

Abstract: URB597 (URB) has therapeutic potential for treating chronic cerebral hypoperfusion (CCH)-induced neuronal death. The present study investigated the protective effects of URB on autopahgy and mitophagy in a CCH model as well as the underlying mechanisms. The ultrastructural changes were examined by electron microscopy. The mitochondrial membrane potential was assessed by immunofluorescence. The expressions of autophagy-related proteins (beclin-1, p62, and LC3), lysosome-related proteins (CTSD and LAMP1), and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…In our previous study [7][8][9][10][11], we found that CCH may contribute to neuronal apoptosis, cognitive impairment, chronic neuroinflammatory responses and abnormal excessive autophagy in the frontal cortex and hippocampus of rats, resulting in cerebral ischemic damage. The fatty acid amide hydrolase inhibitor URB597 (URB) could be a candidate for alleviating chronic intracranial ischemic injury, as it could offer increased selective protection with less risk of the undesirable side effects that have been observed with cannabinoid receptor agonists capable of activating all accessible receptors indiscriminately [7][8][9][10][11]. Thus, we believe that URB might be a promising therapeutic agent for the treatment and management of CCH.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…In our previous study [7][8][9][10][11], we found that CCH may contribute to neuronal apoptosis, cognitive impairment, chronic neuroinflammatory responses and abnormal excessive autophagy in the frontal cortex and hippocampus of rats, resulting in cerebral ischemic damage. The fatty acid amide hydrolase inhibitor URB597 (URB) could be a candidate for alleviating chronic intracranial ischemic injury, as it could offer increased selective protection with less risk of the undesirable side effects that have been observed with cannabinoid receptor agonists capable of activating all accessible receptors indiscriminately [7][8][9][10][11]. Thus, we believe that URB might be a promising therapeutic agent for the treatment and management of CCH.…”
Section: Introductionmentioning
confidence: 94%
“…and 3-MA [3 μg/day, intracerebroventricular (i.c.v.) injection] dosages were selected based on previous studies [11,[23][24][25]. For baseline balance, all experimental rats received the intracerebroventricular catheter implantation.…”
Section: Drug Administrationmentioning
confidence: 99%
See 2 more Smart Citations
“…CCH is found in many cerebrovascular diseases, including AD. Excessive BNIP3-cyt C-and parkin-mediated mitophagy was found in CCH, and the fatty acid amide hydrolase inhibitor URB597 (URB) promotes neuroprotection by inhibiting abnormal excessive autophagy as well as mitophagy [24]. Intriguingly, excessive mitophagy was found in a genetic mouse model of HD [25].…”
Section: Excessive Mitophagy In Peripheral and Nervous System Defectsmentioning
confidence: 99%